Description of Conchyliurus dispar n. sp. (Copepoda, Cyclopoida, Clausidiidae) associated with the bivalve Barnea manilensis (Philippi) from the Yellow Sea with a discussion of the male morphotypes in the genus - Moon, Seong Yong; Kim, Il-Hoi (Zootaxa, 2014)
Conchyliurus dispar, a new species associated with the bivalve Barnea manilensis (Philippi), is described from the intertidal zone of the Yellow Sea. The new species is distinguished from its congeners by a combination of the following characters: the absence of posterolateral processes on the male genital somite, the absence of a dorsal lobe on the female genital double-somite, and the presence of proximal spinules on the ventral surface of the anal somite. Based on a review of the literature on Conchyliurus, we also argue that the male of the new species and possibly all other known species of Conchyliurus consist of two distinct morphotypes, a large male and a small male.